Avaliação de desempenho multicritério como apoio à gestão da diretoria de pesquisa e pós-graduação da Universidade Tecnológica Federal do Paraná, Câmpus Pato Branco: uma perspectiva construtivista - Defaci, Ludmila (2017)
The present work aims to build a unique model of performance evaluation to meet the Research and Graduate Directorate of the Federal Technological University of Paraná, Pato Branco Câmpus, using the MCDA-C vision - Multicriteria Decision Support Methodology Constructivist, taking into account the perceptions of the decision maker through this methodology. The research is characterized as exploratory, descriptive and qualitativequantitative. The instruments used for data collection and analysis are: Knowledge Development Process- Constructivist (Proknow-C) and MCDA-C methodology.In relation to Proknow-C, this process allowed the selection of 15 international articles and 15 national articles aligned to the theme, with the following main results: (i) bibliometric analysis allowed to identify the main authors, articles and periodicals; (ii) the systemic analysis allowed the following results to be obtained: a) the performance evaluation models proposed and/or applied in the researches do not show concern in developing a singular model, specific to the context that gave rise to it, or what is important Measure according to the values of the decision maker; b) it was verified that most of the models carry out the measurement, however, it does not integrate the criteria; c) most of the models allowed to diagnose the strengths and weaknesses of the contexts evaluated; d) the models showed concern in proposing actions to generate improvement actions, highlighting the international portfolio.The following results were obtained through MCDA-C: (i) identification of 64 primary evaluation elements (EPAs) which were explored and discussed, giving rise to 89 action-oriented concepts; (ii) finding two major dimensions of decision-maker concern - quality and management, the first large area of which is related to the research and graduate studies stricto sensu, to the research groups and to the lato sensu graduate studies; And the second is related to the image and internal processes; (iii) creation of 5 maps of means and ends relationships, in which, according to the identified dimensions, operational concerns (means concepts) and strategic concerns (concepts ends) were allocated; (iv) formulation of 51 performance indicators with the full participation of the decision maker; (v) construction of the descriptors by means of ordinal scales and form the reference levels for each indicator; (vi) transformation of ordinals into cardinal (quantitative) scales; (vii) conducting the independence analysis; (viii) construction of value functions; and (ix) determination of replacement rates. It is concluded from the theoretical affiliation adopted that the structuring of the proposed performance evaluation model will be useful to support the management of the UTFPR research and graduate board, Câmpus de Pato Branco, as well as the comparison of the indicators of the Literature with the developed model contributes theoretically to the literature.